A family study of trichotillomania and chronic hair pulling. Issue 2 (10th January 2014) - Keuthen, Nancy J.; Altenburger, Erin M.; Pauls, David
<x xml:space="preserve">Abstract</x> Little is known about the etiology of hair pulling (HP) and its relationship to other obsessive compulsive (OC) spectrum disorders. In a large‐sample family study, we examined the familial aggregation of HP and co‐transmission of obsessive compulsive disorder (OCD) and skin picking (SP). Our sample consisted of 110 proband cases with HP and 48 controls without HP, plus 128 first‐degree case relatives and 50 first‐degree control relatives. Case versus control relatives had higher recurrence risk estimates for both HP and OCD but not SP. The finding that HP is familial is consistent with the only existing twin study. Additional analyses suggest that there may be a familial subtype of HP with comorbid OCD. Those adult proband cases with HP + OCD had more anxiety and depression than cases without OCD. Probands with HP + OCD also had earlier onset of OCD. Identification of an HP subtype with comorbid OCD may have significant theoretical and treatment implications. The data did not provide evidence for an etiologic relationship between HP and SP. Replication of these findings in future studies with larger cohorts of case and control relatives is warranted. © 2014 Wiley Periodicals, Inc.